Relation between «rationality», self-esteem and school achievement in greek high school students - Στογιαννίδου, Αριάδνη; Κιοσέογλου, Γρηγόρης; Χατζηδημητριάδου, Ελένη (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF